2019
DOI: 10.14445/22312803/ijctt-v67i2p104
|View full text |Cite
|
Sign up to set email alerts
|

Security and User Interface Usability of Graphical Authentication Systems – A Review

Abstract: Alphanumeric text and PINs continue to be the dominant authentication methods in spite of the numerous concerns by security researchers of their inability to properly address usability and security flaws and to effectively combine usability and security. These flaws have, however, contributed to the growing research interest in the development and use of graphical authentication systems as alternatives to text based systems. Graphical passwords or graphical authentication systems are password systems that use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Déjà Vu is an algorithm that uses the technology of hash visualization of the images, as shown in Fig. 5(a) [89]. This approach showed that 90% of the participants succeeded in the authentication by using this technique, while only 70% succeeded by using text-based passwords [90].…”
Section: B Graphical Passwordsmentioning
confidence: 99%
“…Déjà Vu is an algorithm that uses the technology of hash visualization of the images, as shown in Fig. 5(a) [89]. This approach showed that 90% of the participants succeeded in the authentication by using this technique, while only 70% succeeded by using text-based passwords [90].…”
Section: B Graphical Passwordsmentioning
confidence: 99%